Ultrasound assisted synthesis of pyrazolo[1,5-a]pyrimidine-antipyrine hybrids and their anti-inflammatory and anti-cancer activities - Kaping, Shunan; Sunn, Melboureen; Singha, Laishram Indira; Vishwakarma, Jai Narain (European Journal of Chemistry, 2020)
A series of antipyrinyl-pyrazolo[1,5-a]pyrimidines have been synthesized by reactions of aminopyrazole (4) with various formylated active proton compounds in the presence of KHSO4 (aqueous media), under ultrasound irradiation. The structures of the compounds have been established with the help of spectral and analytical data. N-(1,5-Dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl)-7-phenylpyrazolo[1,5-a]pyrimidine-3-carboxamide (6a) was further subjected to X-ray crystallographic studies to avoid any ambiguity of the derived structures. Crystal data for compound 6a, C51H46N12O5 (M =907.00 g/mol): triclinic, space group P-1 (no. 2), a = 9.9554(3) Å, b = 14.0875(4) Å, c = 17.4572(4) Å, α = 79.676(2)°, β = 85.283(2)°, γ = 72.647(2)°, V = 2297.97(11) Å3, Z = 2, T = 296.15 K, μ(MoKα) = 0.088 mm-1, Dcalc = 1.311 g/cm3, 29732 reflections measured (4.174° ≤ 2Θ ≤ 57.068°), 10681 unique (Rint = 0.0400, Rsigma = 0.0533) which were used in all calculations. The final R1 was 0.0566 (I > 2σ(I)) and wR2 was 0.1663 (all data). The novel compounds were also screened for their biological activities.